THE HISTORY OF FIEP IN BRAZIL (1949-2010) (Fiep Bulletin - online, 2013)
The history of FIEP in Brazil started in 1949 with the participation of a Delegation composed of 22 Brazilians who represented several states and attended the II STOCKHOLM LINGIADA - Sweden, from July 27 to August 13, 1949, when the FIEP World President, Major Joseph G. Thulin appointed the first FIEP Brazil Delegates, who took the opportunity to invite Prof. Thulin to visit Brazil and other South American countries, what happened the following year. Professors Alfredo Colombo (Rio de Janeiro and eastern Brazil); Sylvio José Raso (Minas Gerais and northern Brazil), Antonio Boaventura da Silva (São Paulo and western Brazil) and Jacintho Francisco Targa (Rio Grande do Sul and southern Brazil), are our pioneers, and had the responsibility to establish and structure FIEP in our country. In 1951 it was held in the city of Santos/SP the first course supported by FIEP Brazil. In 61 years, there have been 265 events with FIEP's logo in 24 states and 53 cities. Promotion, Support and Chancellery of events: Conferences, Tours, Seminars, Workshops, Forums, Meetings and Postgraduate courses. In Brazil, we had four World Congresses.